E-Learning Systems, Environments and Approaches 2015
DOI: 10.1007/978-3-319-05825-2_14
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Improving Information Processing Abilities Based on PBL

Abstract: This study examined an instruction method for the improvement of information processing abilities in elementary school students. Current elementary students are required to develop information processing abilities to create new knowledge for this digital age. There is, however, a shortage of instruction strategies for these information processing abilities.This research proposes a method for teaching information processing abilities based on a problem-based learning model, and was tested with elementary studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Authors referred the benefits of a learning approach applied to students in an introductory level curriculum on computer-aided design, building a bridge between the learning and the curriculum at High School Engineering Education. Kim & Lee (2014) Proposed a method for teaching information processing skills based on a learning model based on problems, and tested in Elementary School students. The author mentions that PBL has an improved methodology for the teaching of skills of information processing.…”
Section: Chao Et Al (2015)mentioning
confidence: 99%
“…Authors referred the benefits of a learning approach applied to students in an introductory level curriculum on computer-aided design, building a bridge between the learning and the curriculum at High School Engineering Education. Kim & Lee (2014) Proposed a method for teaching information processing skills based on a learning model based on problems, and tested in Elementary School students. The author mentions that PBL has an improved methodology for the teaching of skills of information processing.…”
Section: Chao Et Al (2015)mentioning
confidence: 99%
“…The learners will see the problems based on their own prior knowledge and then selecting the reasonable issues and aspects to be more investigated. Kim and Lee (2014) found that his study examined In PBL; the students are challenged to think critically and improve their skill to solve the problem as well as obtain the new essential knowledge and concept of the material. Current elementary students are required to develop information processing skill to create new knowledge for this digital age.…”
Section: Literature Reviewmentioning
confidence: 99%